Exergy return on exergy investment analysis of natural-polymer (Guar-Arabic gum) enhanced oil recovery process. (15th August 2019) - Hassan, Anas M.; Ayoub, M.; Eissa, M.; Musa, T.; Bruining, Hans; Farajzadeh, R.
Abstract: It has been estimated that 17% of the recovered hydrocarbon exergy in oil fields [1 ] is spent on fluid handling and recovery costs. Therefore, improving the efficiency of oil production can give an some contribution to more efficient energy usage and therefore minimizing to some extent the carbon footprint. By way of example we present in this paper a work-flow, which can serve as a template for computing the fluid handling and recovery costs for natural polymer (Guar-Arabic Gum) flooding. The main contributors to the exergy investment in an Exergy Return on Exergy Investment analysis (ERoEI) are, the fluid circulation costs, the steel costs of the tubing and casing and to some degree the drilling costs. The main contributor to the exergy gain is the exergy of the produced oil. The fluid circulation costs represent the largest exergy investment and usually approximately accounts for 80% of the exergy used for the recovery of oil. For quantifying the circulation costs, the paper uses a 1-D displacement model of polymer flooding of oil to compare the enhanced oil recovery (EOR) history for three scenarios, i.e., (1) water injection, (2) natural-polymer water injection and (3) natural-polymer slug injection. The advantage of a 1-D model is that it allows multiple comparisons of many scenario's avoiding time consuming simulations but this goes at the expense of ignoring 3-D effects. The 1-D model can be extended to a 2-D or 3-D model, which makes it possible to include the improvement of vertical and areal sweep-efficiency. A numerical solution of the EOR model is obtained with COMSOL. We analyze the exergy balance of viscosified water, e.g., with natural-polymer. A comparison as to the displacement efficiency is made between the three scenarios, viz., water, Guar-Arabic gum, and slug injection. The viscosity behavior of Guar-Arabic gum is obtained from laboratory data. It is argued that an ERoEI analysis, which is used on its own or complementary to an economic analysis, can be used to show the advantage of using Guar-Arabic gum slugs with respect to permanent polymer-injection to enhance the oil recovery. Moreover, the analysis shows that at the end of the project, the concept of exergy-zero recovery time or zero-time marks, for each scenario the termination point, i.e., when the circulation exergy costs (exergy investment) become equal to the recovery exergy (exergy return), and thus recovery should be abandoned. For the conditions considered a single polymer injection displacement leads to optimal results. Highlights: Using a 1-D model of natural-polymer displacement it is possible to analyse the Exergy Return on Exergy Investment (ERoEI). The investment costs are frequently mainly due to circulation costs (%80) of the exergy used for the recovery of oil. A small rock permeability leads to high circulation costs, thus higher invested exergy costs. The abandonment time occurs before the circulation exergy costs become equal to the recovery exergy costs. A minimum exergy cost corresponds to minimum greenhouse gas emission.